Envisioning contemporary transformation of Lisbon from its metropolitan-regional processes and models. - Robalo, P. (2020)
Lisbon’s new dynamics of urban transformation are generally framed by socially recognizable concerns, such as housing, mobility, public space and heritage, but oblivious to the structural role of metropolitan-regional spatial reorganization. In the context of metropolitan epistemologies, although Lisbon’s functional and relational spaces were never socially and politically recognized as legitimate scales of urbanism, strategy and governance, metropolitan-regional scales have been constructed according to specific urban models and processes rooted in the metropolitan paradigm of centre hegemony and distinction from peripheries. In this paper we’ll argue that a metropolitan-regional vision, reorganization of urban space and territory is intrinsic to Lisbon’s new urban dynamics. And that metropolitan-regional scales of decision and urban policies are - pre-condition and structure – to territorialisation of urban competitiveness and rescaling processes.